Gambaran Pelaksanaan 5 Tugas Kesehatan Keluarga dalam Merawat Lansia dengan Penyakit Gout Arthritis di Desa Talumelito - Amara, Sri Susanti; Febriyona, Rona; Sudirman, Andi Nur Aina (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Background: Problems that often occur in families in caring for gout patients are the family's lack of knowledge about gout and lack of ability to maintain a gout arthritis diet, so to overcome these problems the role of the family is needed in carrying out the five family health tasks in maintaining gout arthritis, the family plays a role in looking after a sick family member, the family needs to be supported by a nurse. Objective: This research is to describe the implementation of 5 family health tasks in treating gouty arthritis in Talumelito Village. Method: The research is quantitative research using a descriptive design with a cross sectional approach. Result: The results of the research showed that before the intervention was given regarding the implementation of the five family health tasks, the three families did not carry out family health tasks well, whereas after the educational intervention was carried out regarding the implementation of the five family health tasks, it was found that 15 families already knew the symptoms and causes of gouty arthritis from one to the other. 15 families also know what diet to follow to prevent recurrence of gouty arthritis, and families use health facilities to check the health of elderly people who suffer from hypertension. Conclusion:nThis research is expected to be used as a basis for further research with different methods so that the results obtained more optimal.